Quality of life of patients with rheumatoid arthritis under biological therapy - Azevedo,Amanda Figueiredo Barbosa (2015)
Summary Objective: assessing health-related quality of life (HRQL) in patients with rheumatoid arthritis (RA), before and after treatment with biological therapy. Methods: a longitudinal study, conducted from November 2010 to September 2011, with implementation of the instruments HAQ II (health assessment questionnaire) and SF-36 (medical outcomes short-from health survey). Barlett test, Anova, Friedman and paired t-test were performed for multiple extracts. Results: 30 patients were evaluated, mean age of 47.6 (SD: 12.25) years and prevalence of females (90%). The mean score of HAQ II before treatment was 1.97, with significant reduction of up to 1.23 after six months of biological therapy (p<0.01). Most of the SF-36 domains showed significant improvement after six months of treatment (p<0.01), highlighting the social aspects, pain, physical functioning, emotional issues, vitality and physical aspects. Conclusion: the use of biologic therapy in patients with RA refractory to standard therapies proved to be an important pharmacological strategy for improving HRQL.